Is peanut causing food allergy in Cuba? Preliminary assessment of allergic sensitization and IgE specificity profile to peanut allergens in Cuban allergic patients - Mayteé Mateo-Morejón; Alexis Labrada-Rosado; Damaris Torralba-Averoff; Rayza Cruz-Jimenez; Yunia Oliva-Díaz; Mirta Álvarez-Castelló; Alexander Ciria-Martín; Marlene Jiménez-Frandín; Mary Carmen Reyes-Zamora; Raúl Lázaro Castro-Almarales; Beatriz Tamargo-García (World Allergy Organization Journal, 2017)
Abstract Background Peanut allergy is increasing at an alarming pace in developed countries. Peanut (Arachis hypogaea) is a common food in Cuba. Nevertheless, reported values of sensitization and symptom severity are usually low. As our objective, we carried out an evaluation of allergic sensitivity to perform an assessment of allergic sensitization and IgE specificity profile to peanut allergens in Cuban allergic patients. Methods The Skin Prick Test (SPT) was performed for each patient, using two glycerinated allergenic extracts, prepared from raw or roasted peanuts. Overall, 316 food allergic patients (159 adults and 157 children) attending allergy services at four hospitals in Havana were included, as well as 303 adult non- allergic volunteers. The IgE binding profile of 26 selected SPT positive patients was further analyzed by immunoblotting. Results The prevalence of sensitization to peanut was 4.6% in general adult population, whereas in adult food-allergic patients it was 18.6%. Prevalence rates were even greater in food allergic children achieving 25.8%. Sensitization frequencies were apparently greater for roasted, as compared to raw peanuts, although the difference was not significant (p> 0.05, Mc Nemar's). IgE binding was shown mostly by the 15 and 17 kDa bands, tentatively identified as the major allergens Ara h 2 and Ara h 6. The IgG4 binding profile was similar to IgE, although with more prominence of the bands at 37 and 28 KDa, corresponding to an Ara h 3 fragment and Peanut Agglutinin. Discussion The study estimated a relatively high prevalence of peanut sensitization in population. Data reported here suggest that IgE sensitization in Cuban patients is focused mostly on MW bands corresponding to the major allergens Ara h 6 and Ara h 2. Conclusions Sensitization to peanut allergen is indeed relatively frequent in Cuba. The IgE profile is congruent to a sensitization pattern by ingestion of roasted peanuts and is directed to well-known major allergens.